Termination Of The Office Of The Land Deed Maker Who Are Otherwise Unable To Perform Their Duties Due To Health Conditions - Muhammad Taufiq; Mohammad Hamidi Masykur; Arini Jauharoh (CV. AFDIFAL MAJU BERKAH, 2024)
The legal issue is motivated by the existence of arrangements related to the dismissal of PPAT with respect contained in Article 10 paragraph (2) letter B which states that PPAT can be dismissed with respect from his position because he is no longer able to carry out his duties due to the state of his health or mental health, after being declared by the authorized health examination team at the request of the Minister/Head or appointed official. The problem then is how when there is a PPAT who is dismissed with respect for health reasons in accordance with Article 10 paragraph (2) letter b, then the PPAT in question successfully recovers from his illness. The purpose of this study was to analyze and find whether PPAT that was dismissed with respect due to health problems can be reappointed after being declared cured and formulate future regulatory formulations related to PPAT dismissal regulations due to health problems. This research uses normative juridical research method, legislation research approach and conceptual approach, and legal materials used consist of primary, secondary, and tertiary legal materials obtained through literature studies in the library of the Faculty of law, Universitas Brawijaya, and also internet access. The results of this study were analyzed by the method of legal discovery, namely the method of interpretation and construction. The results of this study are PPAT dismissed with respect in accordance with Article 10 paragraph (2) letter B PP No. 24 of 2016 if the PPAT has recovered, it still cannot be reappointed to his position as PPAT because there are no rules governing it. This would have been contrary to the theory of legal certainty according to Nurhasanah Ismail. For the formulation of future arrangements related to PPAT dismissal regulations due to health problems can be constructed into a new provision that PPAT who experience health problems, changed from the previous one dismissed with respect, is changed to become a temporary dismissal.